Testing the efficacy of a virtual reality‐based simulation in enhancing users' knowledge, attitudes, and empathy relating to psychosis. (23rd June 2017) - Formosa, Nicholas J.; Morrison, Ben W.; Hill, Geoffrey; Stone, Daniel
Abstract: Objective: The current study examined the efficacy of a virtual reality (VR) education system that simulates the experience of the positive symptomology associated with schizophrenic spectrum and other psychotic disorders. Method: The sample comprised of 50 participants from the general public and various psychology undergraduate programs. Participants completed pre‐test measures exploring knowledge of diagnosis, attitudes, and empathetic understanding, before being exposed to an immersive VR simulation of a psychotic episode. Participants then completed the original measures with the addition of a user‐experience scale, which explored sub‐factors understood to share a relationship with VR effectiveness (i.e., fidelity, immersion, presence, and user buy‐in). Results: Participants' scores were significantly enhanced at post‐test across each outcome measure, with significant correlations found between a number of the gain and user‐experience scores. Conclusions: The findings suggest that VR‐based simulations of psychopathology may offer a promising platform for delivering a constructionist approach to psychology education.